Topical Application of Orabase Bromelain Gel Reduces Inflammatory Process, Bone Loss and Steatosis in Experimental Periodontitis - Even Herlany Pereira Alves; Hélio Mateus Silva Nascimento; Luiz Felipe de Carvalho França; Any Carolina Cardoso Guimarães Vasconcelos; Larissa dos Santos Pessoa; Felipe Rodolfo Pereira da Silva; John Arlley Sousa Pinho de Lira; Paulo Roberto Carneiro Gomes; André dos Santos Carvalho; André Luiz dos Reis Barbosa; Daniel Fernando Pereira Vasconcelos (Brazilian Archives of Biology and Technology)
Abstract This study aimed to develop a bromelain-based gel and evaluate its effects in a ligature-induced periodontitis model in rats. The bromelain-based gel was formulated in two concentrations (1% and 10%). Ten animals were used per group: Control, Periodontitis, Periodontitis + Neutral Gel, Periodontitis + 1% Bromelain Gel, Periodontitis + 10% Bromelain Gel and Periodontitis + 2% Chlorhexidine Gel. The clinical parameters of tooth mobility (TM), gingival bleeding index (GBI) and probing pocket depth (PPD) were evaluated and, after euthanasia, gingival and liver tissue were collected by biopsy for biochemical evaluation of myeloperoxidase (MPO), malonaldehyde (MDA), glutathione (GSH) and from the jaws for morphometric analysis of alveolar bone height. The clinical parameters of MT, GBI and PPD of the groups treated with bromelain gel showed a significant reduction (MT = 67.04%, GBI = 67.72% and PPD = 41.22%) compared to the group with periodontitis. The results for MPO dosage in the gingival tissue showed statistically significant differences between the groups when compared to the group with periodontitis, MDA and GSH showed promising results in the groups treated with gels in the dosages of gingival and liver tissue. The results for ABL showed significant differences when compared to the groups that received gel treatment. Therefore, the bromelain orabase gel evaluated in periodontitis showed a positive response for the following parameters TM, GBI and PPD, MPO, MDA and ABL of the oral tissues, preventing alveolar bone resorption caused by the disease, highlighting the potential as an adjuvant treatment of periodontitis, in addition to reducing the systemic effects on the liver tissue.